2020
DOI: 10.1021/acsomega.0c02873
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Actinide Complexes with Macropa

Abstract: The complex formation of actinium (Ac 3+ ) and californium (Cf 3+ ) ions with macropa (a promising ligand for medical applications, e.g., in targeted α therapy) has been studied by means of density functional theory (DFT) calculations. This work is focused on the structural and bonding properties, the latter on the basis of charge transfer data and topological properties of the electron density distribution. The effect of water solvent on the energetics has been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 95 publications
4
24
0
Order By: Relevance
“…It should be noted that the dissociation energies are likely underestimated by the LC pseudopotential of Ac. In a recent study of the Ac(macropa) complex [34], underestimation by 50 and 48 kJ/mol was found for the electronic (in vacuum) and Gibbs free energies (in solution) of dissociation by the LC pseudopotential (unpublished results). An underestimation in this magnitude would not change the trends in Fig.…”
Section: Energeticsmentioning
confidence: 93%
See 3 more Smart Citations
“…It should be noted that the dissociation energies are likely underestimated by the LC pseudopotential of Ac. In a recent study of the Ac(macropa) complex [34], underestimation by 50 and 48 kJ/mol was found for the electronic (in vacuum) and Gibbs free energies (in solution) of dissociation by the LC pseudopotential (unpublished results). An underestimation in this magnitude would not change the trends in Fig.…”
Section: Energeticsmentioning
confidence: 93%
“…Unfortunately, severe SCF convergence problems occurred with the SC pseudopotential (ECP-60MWB + (14s13p10d8f6g/10s9p5d4f3g) valence basis) of Ac [43,44]; therefore, for this metal, the large-core ECP-78MWB pseudopotential with the contracted (7s6p5d2f1g)/ (6s5p4d2f1g) valence basis [45] set was used. In a recent study on Ac(macropa) complexes including both the SC and LC pseudopotentials for Ac [34], differences in the magnitude of 0.01 Å in the metal-ligand distances and 50 kJ/ mol in the dissociation energies were observed comparing the results obtained by the two Ac pseudopotentials. All the applied pseudopotentials here cover the scalar relativistic effects, which are particularly important for the heavy metals.…”
Section: Computational Detailsmentioning
confidence: 98%
See 2 more Smart Citations
“…Acyclic picolinates H 4 neunpa [20,21] N 5 O 4 RT, 1 h, pH 5.5, 10 À3 M G H 4 phospa [21] N 4 O 4 77 D RT, 1 h, pH 5.5, 10 À3 M H 4 noneunpa [20] N 4 O 5 90 D RT, 1 h, pH 5.5, 10 À6 M H 4 octapa [21] N 4 O 4 20.13 93 D RT, 1 h, pH 5.5, 10 À5 M H 4 CHXoctapa [21] PSMA; [25][26][27][28][29][30] tetrazine-TCO [31] H 4 DOTP [24] N 4 O 4 Capped inverted square prism 408C, 30 min, pH 10, 10 À2 M 18-Crown-6-based H 2 macropa [32,33] N 4 O 6 Irregular tridecahedron 14.99 99 E RT, 5 min, pH 6, 10 À7 M PSMA; [14,34] trastuzumab [14] H 4 crown N 4 O 6 90 RT, 10 min, pH 5-7, 10 À6 M aMSH [35] A From the La 3þ X-ray crystallographic structure.…”
Section: Radiolabelling Conditions F Bioconjugatementioning
confidence: 99%